PENGARUH LITERASI KEUANGAN DAN KEMUDAHAN TRANSAKSI TERHADAP PENGGUNAAN SHOPEE PAYLATER - Kristiastuti, Francisca; Mechi Susilawati; Reza Kurniawan (Jurnal Administrasi Bisnis, 2023)
The increasing use of internet for online shopping has contributed to its popularity. Paylater, a convenient and practical payment method, enables users to finalize purchases instantly and defer payments to a subsequent due date. Nonetheless, prudent utilization of Paylater is crucial to prevent prospective financial complications. Financial literacy is essential for helping people manage their finances successfully and identify potential financial hazards. The aim of this study is to look at how financial literacy and transaction convenience affect the use of Shopee Paylater. The quantitative research method was used, with data collected through a questionnaire distributed to 82 students from the 2020 cohort at Universitas Nurtanio Bandung who use Shopee Paylater. Purposive sampling was used, along with multiple linear regression analysis. The results show that financial literacy has no impact on the utilization of Shopee Paylater. On the other hand, transaction convenience has an effect. Simultaneously, financial literacy and transaction convenience have an impact on the utilization of Shopee Paylater.